Makna Business Intelligence dalam Proses Inovasi Produk: Studi Kualitatif di Industri FMCG - Syahrani Harmi; Muhammad Irwan Padli Nasution (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The Fast-Moving Consumer Goods (FMCG) industry faces rapid market dynamics and intense competition, requiring companies to continuously innovate their products. Business Intelligence (BI) has emerged as a strategic tool that enables companies to collect, analyze, and interpret data to support the product innovation process. This study aims to explore the role of BI in supporting product innovation in the FMCG industry through a qualitative approach. Data were collected through in-depth interviews with product managers and data analysts from several leading FMCG companies in Indonesia. The results show that BI contributes to identifying market trends, understanding consumer preferences, and accelerating the decision-making process in new product development. However, challenges such as complex data integration and the need for skilled human resources in data analysis are barriers to effective BI implementation. This study provides insights into the importance of BI as a catalyst for product innovation and suggests the need for investment in data infrastructure and human resource training to maximize the benefits of BI in the FMCG industry.